2019
DOI: 10.1088/2515-7620/ab491c
|View full text |Cite
|
Sign up to set email alerts
|

Echo chambers in climate science

Abstract: To date, echo chambers in American climate politics have been found to focus on the climate-related policy instrument that is under review. In this paper, we explore how echo chambers change over time, integrating data collected on the federal climate policy network after the first 100 days of the Trump Administration had passed with data collected during two periods during the Obama Administration. We employ Exponential Random Graph (ERG) models to test for the similarity and differences over time in the top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Inconsistencies regarding the use of both terms can also be found in the identified scientific literature. Definitions of the two terms can be found in all sources of categories A and B, except for Paulo (2018), Jasny and Fisher (2019), as well as Titeca and Edmond (2019), which do not explain what is generally understood by the term echo chamber. In contrast, the term filter bubble is defined in all category A and B sources in which it occurs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inconsistencies regarding the use of both terms can also be found in the identified scientific literature. Definitions of the two terms can be found in all sources of categories A and B, except for Paulo (2018), Jasny and Fisher (2019), as well as Titeca and Edmond (2019), which do not explain what is generally understood by the term echo chamber. In contrast, the term filter bubble is defined in all category A and B sources in which it occurs.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly aggravating for nature conservation work when mis-or disinformation influences the public discourse on nature conservation topics (Metson 2018, Paulo 2018, Colston and Thomas 2019. This is underlined, for example, by Jasny and Fisher (2019), who address changes in existing echo chambers of the U.S.-climate-policy-network after Donald Trump became President. The thematic focus of the political echo chambers shifted to the question of whether climate change is humaninduced or not, a consequence of the opinions and policies expressed by Trump on climate change (Jasny and Fisher 2019).…”
Section: What Are Possible Effects Of Echo Chambers and Filter Bubbles On Nature Conservation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, local policy domains with active charter school networks were characterized by information-redundancy and the prevalence of "echo chambers" (Goldie, Linick, Jabbar, & Lubienski, 2014). Echo chambers refer to the tendency of organizations to selectively reference the same sources of information to guide decision-making and are a feature of ideologically homogenous policy networks (e.g., Jasny & Fisher, 2019) Finally, intermediary organizations acted as policy forums, in which actors engage in information transmission (e.g., mediating local information channels, coordinating knowledge sharing, disseminating reports), as well as myriad political activities to extend their influence (Fisher & Leifeld, 2015). Organizations, for example, lobbied politicians, advocated for the network to promote specific programs (e.g., charter management organizations) and advertised their work to boost their status within the network.…”
Section: Example 2: Charter Schools Intermediary Organizations and mentioning
confidence: 99%
“…The enclosing nature of echo chambers has been shown to induce intolerance towards opposing views 11 and quantitative analyses suggest that echo chambers may contribute to the spread of misinformation 1,12 . Corroborating these findings, recent empirical research has shown that echo chambers lead to a misleading of public and political discourse, such as disbelief in climate change 13,14 . Investigating how echo chambers emerge on social media thus offers an important opportunity for understanding and potentially counteracting the occurrence of digital misinformation.…”
mentioning
confidence: 93%